Risk factors for multiple drug resistant tuberculosis relapses - А. S. Аlliluev; O. V. Filinyuk; E. E. Shnayder; P. N. Golubchikov; D. E. Аmichba (Туберкулез и болезни лёгких)
The objective of the study: to identify risk factors for relapses in patients after the effective course of chemotherapy for multiple drug resistant tuberculosis (MDR TB). Subjects and methods. Medical files of 346 adult MDR TB patients were analyzed, they all had the effective treatment as per regimen IV in Tomsk Phthisiopulmonology Medical Center in 2009-2011. They were divided into 2 groups: Group 1 included 35 patients who developed a relapse of tuberculosis over the next 5 years; Group 2 consisted of 311 patients who had no relapse of the disease over the next 5 years. Results. The relapse rate in effectively treated MDR TB patients made 10.1% (35/346 patients). The following social factors contributed to higher chances of the relapse: retirement age (p = 0.045; OR = 2.86 [1.14-7.20]) and disability due to somatic diseases (p < 0.001; OR = 4.82 [2.13-10.90]); while biomedical factors were the following: HIV infection (OR = 19.19 [5.29-69.56]), mental illness (OR = 5.85 [2.27-15.03]), tobacco smoking (OR = 3.16 [1.08-9.20]). People with history of tuberculosis relapses (OR = 12.17 [4.19-35.34]) have higher chances of relapse, as well as those having the following characteristics of the tuberculosis disease during the effective chemotherapy course: destruction of lung tissue (OR = 7.48 [1.76-31.80]), positive results of sputum smear microscopy (OR = 2.91 [1.28-6.61]), persisting bacterial excretion (by culture) after 2 months of chemotherapy (OR = 4.98 [2.41-10.29]).